A data mining approach gives insights of causes related to the ongoing transgene presence in Mexican native maize populations. Issue 2 (7th February 2023) - Ureta, Carolina; González, Edgar J.; Piñeyro-Nelson, Alma; Couturier, Stephane; González-Ortega, Emmanuel; Álvarez-Buylla, Elena R.
ABSTRACT: Mexico is the center of origin of maize and one of the phenomena that imperil maize conservation is transgene presence. Although previous studies have documented transgene presence in Mexican landraces, to date there is no countrywide transgene monitoring protocol, nor systematic analyses assessing which factors could be related with transgene presence and dispersal. In this work, we propose a geographically representative sampling protocol and present empirical data from three sampled states: Mexico City, Oaxaca and Chiapas. To further investigate which environmental and social variables could be associated with transgene presence, we carried out a data mining approach. To assess transgene presence in collected maize samples, we used Real-Time PCR, finding that transgenes were widely distributed across sampled localities: 33% of the localities in Chiapas, 25% in Mexico City and 11% in Oaxaca. The data mining approach allowed us to identify state-specific spatial associations in Chiapas and Oaxaca. In Chiapas, a higher probability of transgene presence appeared related to the coexistence of industrialized maize agriculture, while in Oaxaca it was related with seed exchange. We discuss the importance of implementing a national biomonitoring protocol to increase our understanding of the sources that enable transgene presence and dispersal.